2007
DOI: 10.1016/j.brainres.2007.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological evidence of delayed segmentation in a foreign language

Abstract: Previous studies have shown that segmentation skills are language-specific, making it difficult to segment continuous speech in an unfamiliar language into its component words.Here we present the first study capturing the delay in segmentation and recognition in the foreign listener using ERPs. We compared the ability of Dutch adults and of English adults without knowledge of Dutch ('foreign listeners') to segment familiarized words from continuous Dutch speech. We used the known effect of repetition on the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 25 publications
3
26
2
Order By: Relevance
“…Bosker et al (2017) demonstrated that a carrier sentence is perceived as faster if listeners are taxed by high relative to low cognitive load required for a concurrent visual search task. This supports suggestions that FLs sound fast because they are harder to process; that is, words are harder to segment out of the continuous speech stream (Snijders et al, 2007). Similarly, Bosker and Reinisch (2015) showed that sentences spoken with a foreign accent that are supposedly harder to process than native speech are perceived as faster than native speech.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Bosker et al (2017) demonstrated that a carrier sentence is perceived as faster if listeners are taxed by high relative to low cognitive load required for a concurrent visual search task. This supports suggestions that FLs sound fast because they are harder to process; that is, words are harder to segment out of the continuous speech stream (Snijders et al, 2007). Similarly, Bosker and Reinisch (2015) showed that sentences spoken with a foreign accent that are supposedly harder to process than native speech are perceived as faster than native speech.…”
Section: Discussionsupporting
confidence: 82%
“…Neurophysiological support for delayed segmentation in non-native listeners has been provided by an ERP study by Snijders et al (2007). Analyses of ERP responses to word repetitions in isolation revealed no difference between natives and non-natives: both groups showed a more positive ERP response to later presentations of the same word.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, native Japanese speakers listening to normal English and English-sounding nonsense sentences did not show any evidence of segmentation within the first 300 ms after word onset (Sanders & Neville, 2003b). Studies employing a familiarization paradigm in which words were initially presented in isolation and then in continuous speech indicate that the earliest indication of segmentation for 10-month-old infants is 340 ms after onset (Kooijman, Hagoort, & Cutler, 2005) and in non-native speakers is 515 ms after onset (Snijders, Kooijman, Cultler, & Hagoort, 2007). Taken together these studies indicate that expertise, though not necessarily learning a language as a native speaker, is necessary for the rapid, online segmentation indexed by the early ERP effects.…”
Section: Discussionmentioning
confidence: 99%
“…Snijders et al (2007) have provided neurophysiological evidence that English adults show similar but delayed and reduced segmentation responses to Dutch stimuli compared to Dutch L1. Hence, L2 segmentation is qualitatively different although Dutch and English are highly similar languages.…”
Section: Discussionmentioning
confidence: 99%